Separation of benzene and cyclohexane with mixed solvent using extractive distillation - Richard, B. (Trans Tech Publications Ltd, 2014)
Isothermal Vapour-liquid equilibrium for cyclohexane (1) + benzene (2) binary system, cyclohexane (1) + benzene (2) dimethylformamide (3) ternary system and cyclohexane (1) + benzene (2) dimethylformamide (3) + cosolvent (4) quaternary systems were obtained. The effects of cosolvents (diethyl glycol, dimethylsulfoxide, N-methylformamide) on the performance of dimethylformamide in benzene-cyclohexane separation were studied. The result shows the selected cosolvents suppress the effectiveness of dimethylformamide. The result also shows that the ratio of cosolvents to dimethylformamide affects the separation factor. Â© 2014 Trans Tech Publications, Switzerland.